Individual and community. (May 2021) - Walzer, Michael
This article describes libertarian and communitarian ways of bringing individuals together in a political community, argues that social democracy successfully mediates between these and then asks how to improve upon the unimaginative and compromised versions of social democracy that exist in the world today.